Expanding tracer space for positron emission tomography with high molar activity 18F-labeled α,α-difluoromethylalkanes - Zhao, Qunchao; Telu, Sanjay; Lu, Shuiyu; Pike, Victor W. (Nature communications, 2025)
Positron emission tomography (PET) is an advanced biomedical imaging modality that relies on well-designed radiotracers to report on specific protein targets and processes occurring in living animals and humans. Cyclotron-produced short-lived fluorine-18 ( t 1/2 = 109.8 min) is widely used to radiolabel tracers for PET. Herein we aim to expand the chemical space available for PET tracer development to include structures with 18 F-labeled α,α-difluoromethylalkyl groups. We report an efficient and broad-scope method for labeling such groups with high molar activities based on a single-step radiofluorination of α-bromo-α-fluoroalkanes. The method is applicable to bioactive compounds and drug-like molecules, and is readily automated for radiotracer production. The unique physical and biochemical features of the α,α-difluoromethyl group can now be exploited in the design of new PET tracers. The demand to expand the chemical space for Positron Emission Tomography (PET) tracer development continues to grow. Here, the authors report optimized single-step radiofluorination of α-bromo-α-fluoroalkanes, producing 18F-labeled α,α-difluoromethylalkanes with high molar activity, thus bolstering the prospect for application of this chemotype as PET tracers.